Primary sources and toxicity of PAHs in Milwaukee‐area streambed sediment. (22nd December 2016) - Baldwin, Austin K.; Corsi, Steven R.; Lutz, Michelle A.; Ingersoll, Christopher G.; Dorman, Rebecca; Magruder, Christopher; Magruder, Matthew
Abstract: High concentrations of polycyclic aromatic hydrocarbons (PAHs) in streams can be a significant stressor to aquatic organisms. To understand the likely sources and toxicity of PAHs in Milwaukee‐area streams, streambed sediment samples from 40 sites and parking lot dust samples from 6 sites were analyzed for 38 parent PAHs and 25 alkylated PAHs. Diagnostic ratios, profile correlations, principal components analysis, source‐receptor modeling, and mass fractions analysis were used to identify potential PAH sources to streambed sediment samples, and land‐use analysis was used to relate streambed sediment PAH concentrations to different urban‐related land uses. On the basis of this multiple lines‐of‐evidence approach, coal‐tar pavement sealant was indicated as the primary source of PAHs in a majority of streambed sediment samples, contributing an estimated 77% of total PAHs to samples, on average. Comparison with the probable effect concentrations and (or) the equilibrium partitioning sediment benchmark indicates that 78% of stream sediment samples are likely to cause adverse effects to benthic organisms. Laboratory toxicity tests on a 16‐sample subset of the streambed sites using the amphipod Hyalella azteca (28‐d) and the midge Chironomus dilutus (10‐d) measured significant reductions in 1 or more biological endpoints, including survival, in 75% of samples, with H. azteca more responsive than C. dilutus . Environ Toxicol Chem 2017;36:1622–1635. © 2016 The Authors. Environmental Toxicology and Chemistry Published by Wiley Periodicals, Inc. on behalf of SETAC.